The oxidation of apocynin catalyzed by myeloperoxidase: Proposal for NADPH oxidase inhibition - Ximenes, Valdecir Farias [UNESP]; Kanegae, Marilia P. P.; Rissato, Sandra Regina [UNESP]; Galhiane, Mario Sergio [UNESP] (Elsevier B.V., 2007)
Apocynin has been used as an efficient inhibitor of the NADPH oxidase complex and its mechanism of inhibition is linked to prior activation through the action of peroxidascs. Here we studied the oxidation of apocynin catalyzed by myeloperoxidase (MPO) and activated neutrophils. We found that apocynin is easily oxidized by MPO/H2O2 or activated neutrophils and has as products dimer and trimer derivatives. Since apocynin impedes the migration of the cytosolic component p47phox to the membrane and this effect could be related to its conjugation with essential thiol groups, we studied the reactivity of apocynin and its MPO-catalyzed oxidation products with glutathione (GSH). We found that apocynin and its oxidation products do not react with GSH. However, this thiol compound was efficiently oxidized by the apocynin radical during the MPO-catalyzed oxidation. We suggest that the reactivity of apocynin radical with thiol compounds could be involved in the inhibitory effect of this methoxy-catechol on NADPH oxidase complex. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: apocynin; myeloperoxidase; NADPH oxidase; respiratory burst; hypochlorous acid; neutrophil